PERSEPSI GURU TERHADAP KARAKTER TANGGUNGJAWAB SISWA DALAM PEMBELAJARAN DARING DI SMPN 34 KOTA PEKANBARU - Veni Gracia Sitanggang; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by a phenomenon that arises, namely the teacher's perception of the character of student responsibility during online learning at SMPN 34 Pekanbaru City where online learning also has an impact on the character of student responsibility so that teachers have different perceptions about the character of student responsibility during learning applied online. Based on this background, there is a problem formulation, namely how is the teacher's perception of the character of student responsibility in online learning at SMPN 34 Pekanbaru City. This study aims to determine the teacher's perception of the character of student responsibility in online learning at SMPN 34 Pekanbaru City. The population in this study amounted to 33 people and the sample in this study was 33 people using total sampling technique. The research method used in this study is observation, questionnaires, interviews and documentation in processing research data using quantitative descriptive research. Based on the calculation results, it was found that based on the overall recapitulation of 6 (six) indicators, 10.93% + 56.77% = 67.7% were in the range of 50.01% - 75% = Good. Thus it can be concluded that the teacher's perception of the character of student responsibility in online learning at SMPN 34 Pekanbaru is at the Good level.Key Words: Teacher Perception, Character Of Responsibility, Online Learning.